Multiple principal-agent problems in securitisation - Lui, Alison (Economics and Business Review, 2011)
Every crisis presents opportunities. The financial crisis of 2007-2009 provides a valuable opportunity to study the corporate governance and regulatory aspects of the banking sector, a hinge point in the development of corporate governance in banks. There is a tremendous amount of academic literature on corporate governance of corporations generally, but not of banks. Banks share many characteristics in common with other corporations but differ in respect of the social costs involved. Banks play a fundamental role in a country's economy and problems within the banking sector will have an impact on the wider community. The author argues that corporate governance played an important contributing factor to the financial crisis. In particular, the financial crisis has highlighted multiple principal-agent problems within the 'originate-to-distribute' model of banking. Multiple principal-agent problems are the direct consequence of financial innovation and regulatory dialectic. The 'originate-to-distribute' model relies on securitisation. Academic literature has revealed that securitisation is opaque and complex (Buiter, 2007; Berndt and Gupta, 2008; Fender and Mitchell 2009a). Little research however, has been conducted into why securitisation is opaque and complex from a principal-agent angle. This paper thus provides a new perspective to the literature on principal-agent theory and banking corporate governance. (original abstract)